Fluvoxamine Attenuated Endoplasmic Reticulum Stress-Induced Leptin Resistance - Hosoi, Toru; Miyahara, Tsuyoshi; Kayano, Takaaki; Yokoyama, Shota; Ozawa, Koichiro (Frontiers in Endocrinology, 2012)
Increasing evidence indicates that endoplasmic reticulum stress (ER stress) is involved in the development of metabolic syndrome. However, pharmacological treatments targeting ER stress are not well understood. In the present study, we found that fluvoxamine, a selective serotonin reuptake inhibitor used for depression, can attenuate ER stress-induced “leptin resistance”, i.e. insensitivity to the anti-obesity hormone leptin. Treatment with tunicamycin, an ER stress-inducing reagent, caused cell death which was significantly inhibited by fluvoxamine. Leptin activates JAK2-STAT3 signaling. ER stress caused an impairment of leptin-induced STAT3 phosphorylation which was reversed by fluvoxamine. Fluvoxamine would be a novel leptin-sensitizing drug, which targets ER stress.